Effect of oral isotretinoin therapy on thyroid function in patients with moderate-to-severe acne vulgaris: A prospective study - Fahad AlSaif; Hend AlOtaibi; Amal Balbisi; Ahmad AlAmari; Faisal AlSaif; AlBatool AlAmari; Abdulrhman AlDakhil; Arwa AlModayfer; Nourah AlSyefi (Wolters Kluwer Medknow Publications, 2020)
Introduction: Despite its growing use, the side effects of isotretinoin therapy are not fully understood. Studies have suggested that isotretinoin can cause thyroid dysfunction, suggesting the need to investigate thyroid dysfunction as a possible side effect of oral isotretinoin therapy. Purpose: The main objective of the study is to investigate the association between isotretinoin therapy and thyroid dysfunction. Methods: In all, 51 patients (male, 21; female, 30; aged 18-25 years) with moderate-to-severe acne vulgaris were treated with 0.5 mg/kg/day oral isotretinoin (cumulative dose: 120-150 mg/kg). Serum-free thyroxine (T4), thyroid-stimulating hormone (TSH), and thyroglobulin (TGA) and thyroid peroxidase (TPO) antibody levels were measured. Results: TSH levels at baseline and at the 2nd, 4th, 6th, and 8th months of treatment were 2.3307 ± 1.097, 2.5824 ± 1.34, 2.678 ± 1.133, 2.3 ± 1.17, and 2.7 ± 2.17 IU·mL, respectively, with no significant change from baseline (P = 0.526, P = 0.552, P = 0.530, and P = 0.910 at 2, 4, 6, and 8 months, respectively). Serum levels of free T4, TGA, and TPO antibodies were unchanged. Conclusions: Follow-up screening for thyroid dysfunction may not be necessary for patients receiving oral isotretinoin.